2004
DOI: 10.1007/s00125-004-1403-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and tumor necrosis factor-? are not increased in patients with Type 2 diabetes: evidence that plasma interleukin-6 is related to fat mass and not insulin responsiveness

Abstract: These data show that the increased circulating IL-6 concentrations seen in patients with Type 2 diabetes are strongly related to fat mass and not insulin responsiveness, and suggest that neither IL-6 nor TNFalpha are indicative of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
3
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 50 publications
11
105
3
14
Order By: Relevance
“…103 TNF-a is a strong inducer of lipolysis 104 and data from rodents and humans support a role in the development of insulin resistance. [105][106][107] The latter, however, has been challenged by others 108 and although TNF-a levels are increased in obesity, 109,110 there is little direct release from abdominal subcutaneous adipose tissue in vivo. 111 Interestingly, in a similar set of studies it was found that abdominal subcutaneous adipose tissue releases the soluble TNF receptor type 1 and that its levels correlate with BMI.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…103 TNF-a is a strong inducer of lipolysis 104 and data from rodents and humans support a role in the development of insulin resistance. [105][106][107] The latter, however, has been challenged by others 108 and although TNF-a levels are increased in obesity, 109,110 there is little direct release from abdominal subcutaneous adipose tissue in vivo. 111 Interestingly, in a similar set of studies it was found that abdominal subcutaneous adipose tissue releases the soluble TNF receptor type 1 and that its levels correlate with BMI.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…These pro-inflammatory cytokines can, in turn, act via transmembrane receptors to phosphorylate serine/threonine kinases, which are known to disrupt insulin signal transduction [1]. Given this pro-inflammatory response and the observation that systemic IL-6 concentrations are elevated in obesity and patients with type 2 diabetes [2], it is generally accepted that IL-6 contributes to obesityinduced insulin resistance [3]. However, the discovery that IL-6 can be produced and released from skeletal muscle during exercise, led many investigators, as reviewed by Pedersen and Febbraio [4], to challenge this concept because insulin action is enhanced in the immediate postexercise period.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating and adipose tissue IL-6 levels are increased in patients with obesity, insulin resistance and type 2 diabetes [3][4][5][6][7][8][9], the increased level correlating with degree of insulin resistance measured as insulin-stimulated glucose uptake [7][8][9]. Although difficult to firmly prove, it has been suggested that the increased plasma concentrations of IL-6 in patients with type 2 diabetes are an indicator of the increased fat mass rather than insulin resistance as such [10]. However, it is well established that the adipose tissue is an important source of IL-6 production in man [5].…”
mentioning
confidence: 99%